The Unity and Equality of the Divine Relations in Gregory of Nazianzus' Trinitarian Theology - Sutherland, Grant M. (My University, 2019)
In this thesis, the author examines how Gregory of Nazianzus distinguishes between the Father, Son, and Holy Spirit, while maintaining their equality and unity. In the first chapter, he examines the way theological discourse shapes Gregory's understanding of how words are predicated of God. In chapter 2, the author explores Gregory's understanding of the divine persons whom he distinguishes only on account of their subsistent relations of origin. In the final chapter, the author indicates problems with the modern scholarly interpretation of Gregory that identifies the unity and equality of the divine persons exclusively with the person of the Father. It is concluded that Gregory relied upon the notion of the homoousios in order to establish and guarantee the divine equality and unity among the persons.
Keywords: Trinity; Theology; Patristics; Gregory of Nazianzus